2019
DOI: 10.28933/ijoar-2019-07-2805
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Digital Gameplay for Older Adults: Does Game Type Make a Difference?

Abstract: Digital games can help older adults to entertain themselves, socialize with others, engage their cognitive functions, and enhance emotional states. This study surveyed 463 older Canadian adults to identify the digital games they had played and investigate whether playing them was associated with perceived socioemotional and cognitive benefits. The most widely reported socioemotional benefits were developing self-confidence, dealing with loneliness, and connecting with family. The most widely reported cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…While we specifically asked about communication with friends and family outside the household, we did not distinguish between the type of online game, or with whom people played. Different online gaming experiences have shown to relate differently to social wellbeing (Johnson et al, 2013; Kaufman et al, 2019), thus this could be a fruitful avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…While we specifically asked about communication with friends and family outside the household, we did not distinguish between the type of online game, or with whom people played. Different online gaming experiences have shown to relate differently to social wellbeing (Johnson et al, 2013; Kaufman et al, 2019), thus this could be a fruitful avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anthropologists have suggested that some archeological artifacts originally considered "works of art" or "religious tools" may be pieces of unknown games (Culin, 1907(Culin, /2007Avedon and Sutton-Smith, 1971). Furthermore, gaming is culturally valued (Avedon and Sutton-Smith, 1971;Apostolou et al, 2014;Crist et al, 2016), is associated with physical, cognitive and social benefits (Caillois, 1958(Caillois, /2001Roberts et al, 1959;Zimmer, 1987;Kaufman et al, 2019). It includes specific mental states (Walther, 2003;McGonical, 2011), and is costly due to selfhandicapping rules (Suits, 1978).…”
Section: Play and Games As Stemming From Evolved Propensitiesmentioning
confidence: 99%
“…The report further revealed that 50 percent of players indicated playing digital games daily totaling a weekly gameplay duration of five hours. Older adults play games that are familiar with simple rules, concepts, and interfaces (Chesham, Wyss, Müri, Mosimann & Nef, 2017; Vasconcelos, Silva, Caseiro, Nunes & Teixeira, 2012) such as casual puzzle games and casual action games (Blocker, Wright & Boot, 2014) that rely on mental simulation (Blocker et al, 2014; Chesham et al, 2017; Entertainment Software Association, 2019; Kaufman, Ma, Sauvé, Renaud & Kaufman, 2019; Nap, de Kort & IJsselsteijn, 2009). Older adults are neutral towards action games and dislike first person shooter games (Chesham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%